Factors Influencing Indonesian Sea Transportation Subsidy Policies for Regional Economic Growth - Dimyati Dimyati; Muhammad Zilal Hamzah; Eleonora Sofilda (International Journal of Economics and Management Sciences, 2024)
This research investigates the multifaceted factors influencing Indonesian sea transportation subsidy policies and their impact on regional economic growth. Through a comprehensive literature review and empirical analysis, the study identifies key drivers such as political stability, regulatory efficiency, economic conditions, infrastructure development, and policy implementation mechanisms. Political stability was found crucial for ensuring policy consistency and investor confidence, while efficient regulatory frameworks streamlined subsidy allocations. Economic fluctuations, both global and domestic, significantly influenced resource allocations, underscoring the need for adaptive economic policies. Infrastructure investments emerged as pivotal in enhancing logistics efficiency and reducing operational costs, essential for fostering regional economic competitiveness. Effective policy implementation through transparency, accountability, and monitoring mechanisms was critical in maximizing socio-economic benefits. The findings underscore the importance of integrated policy approaches to address complex challenges and leverage opportunities for sustainable economic development in Indonesia's maritime sector.